1998
DOI: 10.1006/jeth.1997.2384
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Steady States and Endogenous Fluctuations with Increasing Returns to Scale in Production

Abstract: The authors would like to thank very much Jean-Michel Grandmont for valuable comments and suggestions, and for bis constant encouragement. Special grateful thanks to Robin G. de Vilder and Duncan J. Sands for enlightening remarks on our work and for helping with the computer work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 31 publications
4
92
2
1
Order By: Relevance
“…These are quite new results because the widespread view in literature on overlapping generations models is that the rise of periodic orbits and of indeterminacy is due to distortions in the production side of the economy: non perfect competition, positive externalities and so on (see e.g. Reichlin 1986;Grandmont et al 1998;Cazzavillan et al 1998;Cazzavillan 2001), while in our model these dynamic regimes can be observed assuming a very simple production technology (i.e. a Cobb-Douglas one) and perfect competition among firms.…”
Section: Introductionmentioning
confidence: 70%
“…These are quite new results because the widespread view in literature on overlapping generations models is that the rise of periodic orbits and of indeterminacy is due to distortions in the production side of the economy: non perfect competition, positive externalities and so on (see e.g. Reichlin 1986;Grandmont et al 1998;Cazzavillan et al 1998;Cazzavillan 2001), while in our model these dynamic regimes can be observed assuming a very simple production technology (i.e. a Cobb-Douglas one) and perfect competition among firms.…”
Section: Introductionmentioning
confidence: 70%
“…where B > 0 is a scaling parameter [22]. To have a good quality of environment in old age, a representative young consumer invests a portion of her income, d t , in pollution abatement.…”
Section: The Basic Pollution Stock Modelmentioning
confidence: 99%
“…For example, in the cases of productive externalities, imperfect competition in the product market or with consumption, labor or capital taxation, the real interest rate and/or the real wage relevant to consumers' decisions are no longer equal to the marginal productivities of capital and labor at the firm level. Also in the case of consumption or public spending externalities on preferences the relevant intertemporal choice of workers becomes a trade-off between future effective consumption 8 , Ω t+1 L t+1, (that no longer coincides with the wage bill) and leisure. Moreover, in the presence of some labor market imperfections, such as efficiency wages or unions, or with leisure externalities, the private offer curve derived for the perfectly competitive economy is no longer valid at the social level, where the relevant concept is the generalized offer curve Γ.…”
Section: The Modelmentioning
confidence: 99%